2014
DOI: 10.17576/pengurusan-2014-41-13
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Attitude towards Credit Card Usage

Abstract: Credit cards have been viewed as a competitive banking product that helps to improve a bank's financial position

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
(33 reference statements)
2
16
0
1
Order By: Relevance
“…Moreover, the study shows that the convenience and security element that credit cards offer is most important for women. Ismail et al (2014) examined the factors influencing the attitude of bank customers in the context of the Malaysian banking system. The study employed the variable like knowledge, media awareness, perceptions, family influence and religious factors on attitudes towards credit card usage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, the study shows that the convenience and security element that credit cards offer is most important for women. Ismail et al (2014) examined the factors influencing the attitude of bank customers in the context of the Malaysian banking system. The study employed the variable like knowledge, media awareness, perceptions, family influence and religious factors on attitudes towards credit card usage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…El nivel de conocimiento y la educación financiera también son determinantes del uso de tarjetas de crédito (Ismail et al, 2014;Hayhoe, Leach, Allen, y Edwards 2005), así como las influencias familiares y de los medios de comunicación (Ismail et al, 2014). Las actitudes individuales también afectan la decisión de uso de las tarjetas de crédito.…”
Section: Revisión De Literaturaunclassified
“…It shows there is available information about plastic money. In their study, Ismail et al (2014) found that most of the respondents get knowledge about ATM cards from the bank. 3 shows that the majority of the respondents have a debit card.…”
Section: Knowledge About Plastic Money By the Usersmentioning
confidence: 99%